Evaluation of the Effectiveness of Three Interventions on Mineralization of Young Permanent Teeth Using DIAGNOdent™ Pen: A Double-Blind Randomized Controlled Trial - Akshata Agnihotri; K.V.V. Prasad; Shweta Sharda; Lamea Afnan (Wolters Kluwer Medknow Publications, 2024)
Background: The occurrence of dental caries is influenced by the interplay of host factors, microbial factors, and environment factors collectively forming the epidemiological triad of dental caries. Modification of the caries epidemiological triad limits the caries progression by shifting the equilibrium toward re-mineralization. Aim: The aim of this study was to evaluate the effectiveness of dietary sugar intake modification, plaque control measures, and fluoride toothpaste on the mineralization of enamel using DIAGNOdent™ pen scores. Methodology: 108 children aged 13-15 years, qualified the preset inclusion and exclusion criteria were randomly allocated into one among the three interventional groups such as Group 1: Diet counseling; Group 2: Educational intervention of toothbrushing and oral rinsing; and Group 3: Fluoride toothpaste. The sugar scores from 1 week's diet history, plaque index scores, the weight of the fluoride toothpaste, and DIAGNOdent™ pen scores were recorded at the baseline visit and subsequently at 6- and 12-week intervals. Statistical analysis was done using Chi-square, repeated measure analysis of variance, and Tukey's post hoc tests to determine the relationship between the variables. Results: The percentage reduction in DIAGNOdent pen score at 12-week time interval in Group 1 was 25.37%, Group 2 was 6.77%, and Group 3 was 13.37%. Intergroup comparison revealed that Group 1 showed a statistically significant difference (P < 0.05) as compared to Group 2 and Group 3, but Group 2 was as effective as Group 3 in teeth remineralization. Conclusion: the results suggest that among the abovementioned interventions, the dietary sugar restriction group is related to improved mineralization when compared to the instructed toothbrushing, oral rinsing, and fluoride toothpaste groups.